Correlation of Platelet Count and Hematocrit Levels to the Severity of Dengue Hemmoraghic Fever Patients at RSD dr. Soebandi Jember - Salma Naqiyyah Tirtadevi; Rini Riyanti; Desie Dwi Wisudanti (Faculty of Medicine, University of Jember, 2021)
Dengue hemorraghic fever (DHF) is an infectious disease caused by the dengue virus and It is still be a major health problem in Southeast Asia, especially in Indonesia. Kabupaten Jember is still categorized as a dengue endemic area with its disease development expanding from year to year. This study aims to determine the correlation of platelet count and hematocrit levels to the severity of DHF patients at RSD dr. Soebandi Jember, as well as knowing whether the platelet count and hematocrit levels can be used as a predictive value for the severity of DHF patients at RSD dr. Soebandi Jember. This study used an observational analytic study with a cross-sectional study design. The data of this study used secondary data from the medical records of DHF patients at RSD dr. Soebandi Jember. The results of this study with a total of 68 samples showed that there was a significant negative correlation between the platelet count to the severity of DHF patients (p = 0,000, r = -0,487). The hematocrit levels showed an insignificant and negative correlation to the severity of DHF patients (p = 0,658, r = -0,055). The platelet count can be used as a predictive value for the severity of DHF patients. Keywords: DHF, platelet count, hematocrit levels, severity of DHF patients